Perceived Teaching Creativity and Observed Implementation of Creativity in Distance Learning Activities - Adhiwiguna, I Made Agus; Artini, Luh Putu; Wahyuni, Luh Gede Eka (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Creativity was significant in distance learning. As its importance, the teachers had to promote themselves of having a good creativity level in teaching. However, the teachers still lack variation in teaching.  Therefore, this research aimed to analyze the teachers’ perception and teachers’ observed teaching creativity in distance learning. The focus of the research was to identify the discrepancy between teachers’ perceptions and facts as observed in teaching creativity in the classroom. This research applied an embedded mix method. The data collection was done by using questionnaires, observation, and in-depth interviews. English teachers were chosen as the research subject. The data were analyzed quantitatively. The result demonstrated that  teachers perceived themselves as moderately creative in conducting distance learning. Teachers were categorized as unlikely creative in conducting distance learning. The discrepancy occurred since, on the one hand, teachers perceived themselves as moderately creative, while on the other hand, they did not meet the category of a creative teacher. It can be interpreted that teachers need to improve their creativity to avoid monotonous learning activities.